Micro Metal Additive Manufactured Low-Loss Slotted Rectangular Waveguides Operating at 220-500 GHz - Wu, Zixian; Shi, Guanghua; Yu, Yang; Wen, Xiaozhu; Guo, Cheng; Zhang, Anxue (Frontiers in Physics, 2021)
This paper reports the design, fabrication and measurement techniques for a set of low-loss slotted waveguides. The waveguides are fabricated based on a micro metal additive manufacturing technology. They were fabricated layer by layer in one piece without the need of post-fabrication assembly. As examples, straight waveguides in WR-3.4 (220-330 GHz) and WR-2.2 (330-500 GHz) bands were fabricated and tested. Measurement results show the insertion loss per unit length is 0.0615-0.122 dB/mm and 0.116-0.281 dB/mm, respectively.